(untitled) (Journal of Information and Communication Technology, 2021)
Quran has been the focus of many computer science and computational linguistics researchers. However, insufficient contribution is directed towards Quranic readings. This field focuses on the different ways in which Quranic words can be recited. Quranic readings gathering is a recitation process that is well-known by the specialists in this field. In this process, all the possible ways of reading a verse are covered in a compact and well-structured manner. To the best of the author’s knowledge, no computational automation has been cited for this process in literature. In this paper, this process was algorithmically formulated and a developed software system was presented to automate this process. This system took Quranic verse texts as input and generated a text file containing the detailed gathering of the readings of this verse as done by a specialised reciter. The system was applied to the verses of Surah Al-Baqarah and the output text was carefully validated against authentic books in this field. This system can be the basis of software systems for teaching and vocal construction of Quranic readings gathering. It would be useful for students who are interested in Quranic readings.